Molecular engineering on a MoS2 interlayer for high-capacity and rapid-charging aqueous ion batteries. Issue 9 (24th April 2023) - Han, Xuefei; Yang, Jing; Zhang, Yong-Wei; Yu, Zhi Gen
Abstract : Intercalated CO2 molecules can expand the interlayer spacing of layered materials, resulting in high-capacity and rapid-charging aqueous ion batteries. Abstract : Rechargeable aqueous ion batteries (AIBs) play essential roles in the increasing demand for high-performance energy storage systems, and yet they are hampered by the lack of suitable cathode materials because of the sluggish intercalation kinetics. In this work, we develop an effective and feasible strategy to enhance the performance of AIBs by broadening the interlayer spacing by using intercalated CO2 molecules to promote the intercalation kinetics by using first principles simulations. Compared with pristine MoS2, the intercalation of CO2 molecules with a 3/4 ML coverage significantly increases the interlayer spacing to 9.383 Å from 6.369 Å and the diffusivity is boosted by 12 orders of magnitude for Zn ions, 13 orders for Mg ions and one order for Li ions. Moreover, the concentrations of intercalating Zn, Mg and Li ions are enhanced by 7, 1 and 5 orders of magnitude, respectively. The significantly increased diffusivity and intercalation concentration of metal ions signify that intercalating CO2 bilayer MoS2 is a promising cathode material to realize metal ion batteries with a rapid charging capability and high storage capacity. The strategy developed in this work can be generally applied to increase the metal ion storage capacity in transition metal dichalcogenide (TMD)- and other layered material-based cathodes and make them promising for next-generation rapidly rechargeable batteries.